Appropriate Complementary Feeding Among Indonesian Children Aged 6-23 Months: A Descriptif Literature Review - Suyitno, Suyitno; Maretalinia, Maretalinia; Khan, Muhammad Uzair; supriatin, Supriatin (Yayasan Ahmad Mansyur Nasirah, 2024)
The introduction of complementary foods (CF), which includes solid and semi-solid foods alongside breastfeeding, is crucial for ensuring adequate nutrition and supporting healthy growth and development in children aged 6-23 months. In Indonesia, a country with diverse cultures and socioeconomic conditions, family dynamics significantly influence practices and choices related to CF. These factors collectively shape the nutritional status and health outcomes of children during this critical developmental period. This descriptive literature review was conducted by searching electronic databases such as PubMed, Google Scholar, and local Indonesian academic repositories. Keywords used included